Comparison of ultrasound assessment for diaphragmatic workload during spontaneous breathing trial between automatic tube compensation and pressure support ventilation: Study protocol - Kulkanokwan, Nutarpa; Morakul, Sunthiti; Pisitsak, Chawika; Theerawit, Pongdhep (Clinical Critical Care, 2022)
Background: The process of weaning from mechanical ventilation is crucial. Less demanding spontaneous breathing trials (SBT) can be done by either automatic tube compensation (ATC) or pressure support ventilation (PSV) to decrease inspiratory effort by endotracheal tube resistance compensation. This study aimed to assess the patient’s effort, by diaphragm ultrasonography with ATC compared to PSV during SBT. Methods: Patients who have been on mechanical ventilation for more than 48 hours and meet the weaning requirements are given 30 minutes for ATC and 30 minutes for PSV in this randomized control experiment. The diaphragm workload difference, as assessed by diaphragm thickness fraction, was the primary outcome. The sensitivity and specificity of ultrasound-measured diaphragmatic muscle activity measures in predicting ventilator weaning and effective extubation were secondary outcomes. Hypothesis: Intubated patients should be (1) weaning with lower effort SBT mode (2) predicted weaning success with more accurately parameters Ethics and dissemination: Ramathibodi Human Research Ethics Committee has approved the trial. The findings plan to summitted in peer-reviewed publications and conferences in critical care medicine or anesthesiology. Trial registration number: TCTR20210317004